Functional Potential and Chemical Profile Analysis of Propolis Oil Extracted from Propolis of Balochistan - Saliha Aziz; Ali Akbar; Zareen Gul; Muhammad Bilal Sadiq; Jahangir Khan Achakzai; Nazir Ahmad Khan; Abdul Samad; Zia Ur Rehman; Imran Ali (Journal of Food Quality)
Propolis oil (PO) was examined for chemical composition, phenolic and flavonoid content, and antioxidant and antimicrobial potential. Phenolic and flavonoid contents were 2.388 ± 1.116 mg GAE/g and 0.579 ± 0.140 mg QE/g. Oil showed 64.59 ± 14.59% inhibition of DPPH radical and significant antibacterial activities against target bacteria. Salmonella typhi was found to be highly sensitive (27.23 ± 4.35 mm) to PO, compared to Escherichia coli (23.40 ± 3.21), Staphylococcus aureus (21.43 ± 2.80), and Klebsiella pneumoniae (21.26 ± 3.25). The MIC and MBS values of PO were 0.35 and 0.7 mg/mL for S. typhi and E. coli, whereas they were 0.7 and 1.4 mg/mL for S. aureus. Moreover, the PO was found to be bacteriostatic for K. pneumoniae. Aspergillus flavus was found to be highly sensitive to PO, with an effective growth inhibition percentage of 73%, followed by Aspergillus niger (70%), whereas Aspergillus parasiticus was less sensitive with 25% growth inhibition. Functional groups in PO were determined with an FTIR spectrophotometer, and alcohol, alkane, aldehydes, alkenes, and ketones groups were found to be present, whereas GC-MS analysis revealed the presence of 27 different medicinal compounds, among which α-copanene (29.85%), benzyl benzoate (26.8%), 2,4-bis[1-(4-hydroxyphenyl)isopropyl]phenol, acetophenone (14.92%), undecylenic aldehyde (7.46%), p-linalool (5.9%), and ethyl 3-phenylpropionate (4.47%) were found in abundance.